ECONOMIC NATURE OF THE INVESTMENT PROCESS - Andrusiv, U. Y.; Sydor, H. V. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2019)
Purpose. Investigation of the essence of the investment process from the standpoint of existing approaches to economic science in order to formulate its own interpretation of the outlined definition. Methodology of research. Theoretical and methodological basis of the research is the scientific works of domestic and foreign authors on the research of the essence of the investment process, Internet resources. In the process of research used general and special methods, in particular: monographic – in the implementation of the literary review of the problem under study; systematic and structural analysis – in substantiating different approaches and different points of view before interpreting the essence of the investment process as a complex economic category. Findings. Generalized theoretical developments of domestic and foreign scientists-economists on the interpretation of the «investment process». On the basis of systematization of scientific approaches, the actual definition of the term «investment process» is proposed. The research of those scientists who consider the definition of «investment process» at micro and macro levels is considered. The signs that characterize the investment process are presented. Originality. The author’s definition of the term, according to which the investment process should be considered as a never-ending in space and a continuous process of realization of investment decisions connected with attraction of funds, is proposed in order to achieve the goals and maximize the positive result for the participants and the investor. Practical value. The obtained research results are the basis for solving practical problems of the correct scientific approach to understanding this concept at the present stage.